1999
DOI: 10.1038/emm.1999.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceramide on apoptosis and phospholipase D activity in FRTL-5 thyroid cells

Abstract: Ceramide, a product of sphingomyelin hydrolysis, is now recognized as an intracellular lipid messenger, which mediates the effects of extracellular agents on cellular growth, differentiation and apoptosis. Recently, ceramide has been implicated in the regulation of phospholipase D (PLD). In this study, we examined the effects of ceramide on the activity and mRNA level of PLD during apoptotic process in FRTL-5 thyroid cells. C 2 -ceramide (N-acetyl sphingosine) induced apoptosis in FRTL-5 thyroid cells. Fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Around the same time, a partial inhibition of phorbol ester-induced PLD activity by C 2 -ceramide was reported to occur in human neutrophils [101], as well as a partial inhibition of PLD activity by C 2 -and C 6 -ceramide in fibroblasts stimulated with phorbol esters and thrombin [102]. These results have been substantiated by numerous other studies that showed inhibition of PLD by C 2 -ceramide or by C 6 -ceramide and ceramide generated by exogenous SMases [103][104][105][106][107][108][109][110][111][112][113][114][115][116]. Stimulation of cells with agonists that activate PLD has been shown to correlate with the translocation or association of PLD activators to membrane surfaces.…”
Section: Regulation Of Pld By Ceramidesupporting
confidence: 68%
“…Around the same time, a partial inhibition of phorbol ester-induced PLD activity by C 2 -ceramide was reported to occur in human neutrophils [101], as well as a partial inhibition of PLD activity by C 2 -and C 6 -ceramide in fibroblasts stimulated with phorbol esters and thrombin [102]. These results have been substantiated by numerous other studies that showed inhibition of PLD by C 2 -ceramide or by C 6 -ceramide and ceramide generated by exogenous SMases [103][104][105][106][107][108][109][110][111][112][113][114][115][116]. Stimulation of cells with agonists that activate PLD has been shown to correlate with the translocation or association of PLD activators to membrane surfaces.…”
Section: Regulation Of Pld By Ceramidesupporting
confidence: 68%
“…PLD activity was determined by the formation of phosphatidylethanol (PEt) as described elsewhere (Park et al, 1999). Briefly, A20 cells cultured on 6-well plates were metabolically labeled with 1 µCi/ml of [ 3 H]-palmitic acid in serum free medium for 18 h. The cells were then pretreated with 1%(v/v) ethanol for 15 min before stimulation with anti-Fas mAb.…”
Section: Determination Of Pld Activitymentioning
confidence: 99%
“…Assay of PLD activity was based upon the unique ability of this enzyme to stimulate transphosphatidylation in the presence of ethanol to form the corresponding PEth (Kang et al, 1998;Park et al, 1999). M-1 cells were labeled with [ 3 H]myristic acid (1 µCi/ml) for 16 h. The cells were washed twice by phosphate buffered saline (PBS) and resuspended in assay buffer (20 mM Hepes, pH 7.4, 137 mM NaCl, 2.7 mM KCl, 3 mM MgCl 2 , 2 mM CaCl 2 , 2 mM EGTA, and 1 mg/ml bovine serum albumin).…”
Section: Measurement Of Pld Activitymentioning
confidence: 99%